Phase Ia clinical evaluation of the safety and immunogenicity of the Plasmodium falciparum blood-stage antigen AMA1 in ChAd63 and MVA vaccine vectors. - Sheehy, S; Duncan, C; Elias, S; Biswas, S; Collins, K; O'Hara, G; Halstead, F; Ewer, K; Mahungu, T; Spencer, A; Miura, K; Poulton, I; et al. (Public Library of Science, 2012)
BACKGROUND: Traditionally, vaccine development against the blood-stage of Plasmodium falciparum infection has focused on recombinant protein-adjuvant formulations in order to induce high-titer growth-inhibitory antibody responses. However, to date no such vaccine encoding a blood-stage antigen(s) alone has induced significant protective efficacy against erythrocytic-stage infection in a pre-specified primary endpoint of a Phase IIa/b clinical trial designed to assess vaccine efficacy. Cell-mediated responses, acting in conjunction with functional antibodies, may be necessary for immunity against blood-stage P. falciparum. The development of a vaccine that could induce both cell-mediated and humoral immune responses would enable important proof-of-concept efficacy studies to be undertaken to address this question. METHODOLOGY: We conducted a Phase Ia, non-randomized clinical trial in 16 healthy, malaria-naïve adults of the chimpanzee adenovirus 63 (ChAd63) and modified vaccinia virus Ankara (MVA) replication-deficient viral vectored vaccines encoding two alleles (3D7 and FVO) of the P. falciparum blood-stage malaria antigen; apical membrane antigen 1 (AMA1). ChAd63-MVA AMA1 administered in a heterologous prime-boost regime was shown to be safe and immunogenic, inducing high-level T cell responses to both alleles 3D7 (median 2036 SFU/million PBMC) and FVO (median 1539 SFU/million PBMC), with a mixed CD4(+)/CD8(+) phenotype, as well as substantial AMA1-specific serum IgG responses (medians of 49 µg/mL and 41 µg/mL for 3D7 and FVO AMA1 respectively) that demonstrated growth inhibitory activity in vitro. CONCLUSIONS: ChAd63-MVA is a safe and highly immunogenic delivery platform for both alleles of the AMA1 antigen in humans which warrants further efficacy testing. ChAd63-MVA is a promising heterologous prime-boost vaccine strategy that could be applied to numerous other diseases where strong cellular and humoral immune responses are required for protection. TRIAL REGISTRATION: ClinicalTrials.gov NCT01095055.